Precise targeting of transcriptional co-activators YAP/TAZ annihilates chemoresistant brCSCs by alteration of their mitochondrial homeostasis - Priyanka Dey Talukdar; Kunal Pramanik; Priya Gatti; Pritha Mukherjee; Deepshikha Ghosh; Himansu Roy; Marc Germain; Urmi Chatterji (Signal Transduction and Targeted Therapy)
Abstract Persistence of drug-resistant breast cancer stem cells (brCSCs) after a chemotherapeutic regime correlates with disease recurrence and elevated mortality. Therefore, deciphering mechanisms that dictate their drug-resistant phenotype is imperative for designing targeted and more effective therapeutic strategies. The transcription factor SOX2 has been recognized as a protagonist in brCSC maintenance, and previous studies have confirmed that inhibition of SOX2 purportedly eliminated these brCSCs. However, pharmacological targeting of transcription factors like SOX2 is challenging due to their structural incongruities and intrinsic disorders in their binding interfaces. Therefore, transcriptional co-activators may serve as a feasible alternative for effectively targeting the brCSCs. Incidentally, transcriptional co-activators YAP/TAZ were found to be upregulated in CD44+/CD24-/ALDH+ cells isolated from patient breast tumors and CSC-enriched mammospheres. Interestingly, it was observed that YAP/TAZ exhibited direct physical interaction with SOX2 and silencing YAP/TAZ attenuated SOX2 expression in mammospheres, leading to significantly reduced sphere forming efficiency and cell viability. YAP/TAZ additionally manipulated redox homeostasis and regulated mitochondrial dynamics by restraining the expression of the mitochondrial fission marker, DRP1. Furthermore, YAP/TAZ inhibition induced DRP1 expression and impaired OXPHOS, consequently inducing apoptosis in mammospheres. In order to enhance clinical relevance of the study, an FDA-approved drug verteporfin (VP), was used for pharmacological inhibition of YAP/TAZ. Surprisingly, VP administration was found to reduce tumor-initiating capacity of the mammospheres, concomitant with disrupted mitochondrial homeostasis and significantly reduced brCSC population. Therefore, VP holds immense potential for repurposing and decisively eliminating the chemoresistant brCSCs, offering a potent strategy for managing tumor recurrence effectively.